Peripapillary hyperreflective ovoid mass-like structures: multimodal imaging and associated diseases - Xiao, Di; Lhamo, Tsering; Meng, Yang; Xu, Yishuang; Chen, Changzheng (Frontiers in Neurology, 2024)
Growing evidence has demonstrated that peripapillary hyperreflective ovoid mass-like structures (PHOMS) are novel structures rather than a subtype of optic disc drusen. They correspond to the laterally bulging herniation of optic nerve fibers and are believed to be the marker of axoplasmic stasis. PHOMS present in a broad spectrum of diseases, including optic disc drusen, tilted disc syndrome, papilloedema, multiple sclerosis, non-arteritic anterior ischemic optic neuropathy, optic neuritis, Leber hereditary optic neuropathy, and so on. We focus on the multimodal imaging features, pathophysiological mechanisms of PHOMS, and their association with multiple diseases and healthy people in this review to deepen the ophthalmologists' understanding of PHOMS. Additionally, we provide some new directions for future research.